Turkish fingerspelling recognition system using Generalized Hough Transform, interest regions, and local descriptors - Altun, Oguz; Albayrak, Songul (ELSEVIER, 2011)
This paper presents a computer vision system that can recognize Turkish fingerspelling sign hand postures by a method based on the Generalized Hough Transform, interest regions, and local descriptors. A novel method for calculating the reference point for the Generalized Hough Transform, and a simpler but more effective Hough voting strategy are proposed. The stages of implementing a Generalized Hough Transform are examined in detail, and the issues that affect the method success are discussed. The system is tested on a data set with 29 classes of non-rigid hand postures signed by three different signers on non-uniform backgrounds. It attains a 0.93 success rate. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Generalized Hough Transform; DoG; SIFT; Interest regions; Local descriptors; Fingerspelling recognition; FEATURES; Computer Science